V-W inorganic porous material as well as preparation method and application thereof
By developing V-W inorganic porous materials, the problem that existing catalysts cannot effectively remove NOx at room temperature is solved, efficient NO oxidation is achieved, and energy waste and carbon emissions are reduced.
Patent Information
- Application Number
- CN202411963417.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
Existing NO oxidation catalysts cannot effectively remove NOx at room temperature, resulting in increased energy waste and carbon emissions.
A class of V-W inorganic porous materials has regular pore structure, rich acidity and redox properties, and is prepared by hydrothermal synthesis and ion exchange method, and is used for NO oxidation at room temperature.
At room temperature, the V-W inorganic porous material exhibits excellent NO oxidation activity, with a NO conversion rate of 5 to 60%, and can maintain activity for more than 70 hours, significantly improving the efficiency of NOx removal.
Smart Images

Figure CN119898819A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a VW inorganic porous material and a preparation method and application thereof, belonging to the technical field of low-temperature denitration catalysts. Background Art
[0002] NO X As one of the main components of air pollutants, NO X Emissions can cause a series of environmental problems, such as inducing human diseases, damaging human organs, causing photochemical smog, acid rain and other environmental pollution phenomena, destroying the ozone layer, and also causing O3, PM 2.5 NOx is the main precursor of secondary pollutants such as nitrogen oxides and nitrogen oxides, so its removal is urgent.
[0003] At present, the methods widely used in industry to remove NOx mainly include dry denitrification technology and wet denitrification technology. Dry denitrification technology includes NH3 selective catalytic reduction technology (NH3-SCR) and selective non-catalytic reduction technology (SNCR), which mainly treats flue gas discharged from fixed sources such as thermal power plants and industrial furnaces and mobile sources such as automobiles and ships. SNCR technology generally requires the flue gas treatment temperature to be between 800 and 1100°C. The most commonly used NH3-SCR technology also has high requirements for the reaction temperature. At present, the minimum SCR denitrification temperature in industry needs to be completed at more than 180°C, and the research on room temperature denitrification technology is still in a blank stage. However, for some chemical industries (such as nitric acid manufacturing), coal mining industries, small enterprises, etc., the exhaust flue gas temperature is room temperature, and wet denitrification technology is usually used to remove NOx. Wet flue gas denitrification uses the principle of dissolving NOx with a liquid absorbent to purify the flue gas. The biggest obstacle is that NO is difficult to dissolve in water, and it is often required to first oxidize NO to NO2, and then NO2 is absorbed by water or alkaline solution to achieve flue gas denitrification. In summary, the oxidation of NO to NO2 plays an important role in room temperature NOx removal technology, so the efficient oxidation of NO at room temperature has always been the research focus of denitrification catalysts.
[0004] Currently, NO oxidation catalysts are mainly divided into supported catalysts, multi-metal oxide catalysts and perovskite catalysts. At present, the temperature range of these three types of catalysts is mainly concentrated above 300°C, which will undoubtedly cause energy waste and significantly increase carbon emissions. Therefore, the research and development of NO oxidation catalysts at room temperature has become very necessary to reduce carbon emissions and avoid energy waste. Summary of the invention
[0005] Purpose of the invention: The first purpose of the present invention is to provide a type of VW inorganic porous material with a regular pore structure, rich acidity and redox properties. The second purpose of the present invention is to provide a method for preparing the VW inorganic porous material, wherein the raw materials of the preparation method are cheap and readily available, the resources are abundant, and the energy consumption is low. The third purpose of the present invention is to provide the application of the VW inorganic porous material in NO oxidation at room temperature, thereby overcoming the problem that the existing NO oxidation catalyst cannot achieve NO oxidation at room temperature.
[0006] Technical solution: The VW inorganic porous material of the present invention has a general formula of an anion molecule of [W x Mo 4-x V y Zr 3-y O 19 ] 2- or [W x Mo 4-x V y Ti 3-y O 19 ] 2- , where x = 3.2 to 4, y = 2 to 3, and the counter cation is K + , Cs + and H + .
[0007] Furthermore, [W x Mo 4-x O 16 ] 8- The tetrahedral structural unit and VO5 linker form a porous structure similar to type A molecular sieve, whose space group is PA-3 and the lattice parameter is
[0008] Further, the VW inorganic porous material comprises:
[0009] abbreviation Molecular formula Molecular weight Space group HVW-MC <![CDATA[H2W4V3O 19 ]]> 1194.24 PA-3 KVW-MC <![CDATA[K2W4V3O 19 ]]> 1270.42 PA-3 Cs-VW-MC <![CDATA[Cs2W4V3O 19 ]]> 1458.04 PA-3 H-Ti-W-MC <![CDATA[H2W4V2TiO 19 ]]> 1191.18 PA-3 H-Zr-W-MC <![CDATA[H2W4V2ZrO 19 ]]> 1234.52 PA-3 <![CDATA[H-V-Mo 0.2 -MC]]> <![CDATA[H2W 3.8 Mo 0.2 V3O 19 ]]> 1176.66 PA-3 <![CDATA[H-V-Mo 0.4 -MC]]> <![CDATA[H2W 3.6 Mo 0.4 V3O 19 ]]> 1159.08 PA-3 <![CDATA[H-V-Mo 0.6 -MC]]> <![CDATA[H2W 3.4 Mo 0.6 V3O 19 ]]> 1141.50 PA-3 <![CDATA[H-V-Mo 0.8 -MC]]> <![CDATA[H2W 3.2 Mo 0.8 V3O 19 ]]> 1123.92 PA-3
[0010] Furthermore, the VW inorganic porous material has a cubic structure and a crystal size of about 40 to 50 nm.
[0011] Furthermore, the VW inorganic porous material exhibits NO oxidation activity at low temperatures of 20 to 100°C, with a NO conversion rate of 5 to 60%. It has excellent NO oxidation activity at room temperature and can maintain activity for more than 70 hours.
[0012] A method for preparing the VW inorganic porous material of the present invention comprises the following steps:
[0013] (A1) mixing KOH solution and ammonium metatungstate, adjusting the pH, adding VOSO4 solution, continuing to stir, adjusting the pH again, heating to react, centrifuging, collecting the suspension, centrifuging again, drying, and grinding to obtain KVW-MC inorganic porous crystals;
[0014] (A2) mixing KVW-MC inorganic porous crystals with water to form a suspension, adjusting the pH, stirring the suspension, centrifuging, drying, and grinding to obtain HVW-MC inorganic porous crystals;
[0015] (A3) mixing KVW-MC inorganic porous crystals with water to prepare a suspension, adding CsCl, stirring for reaction, centrifuging, drying, and grinding to obtain Cs-VW-MC inorganic porous crystals;
[0016] (A4) mixing KVW-MC inorganic porous crystals with water to prepare a suspension, dropping an aqueous solution of Ti(SO4)2 or Zr(SO4)2, adjusting the pH, stirring the reaction, centrifuging, acid-washing, water-washing, drying, and grinding to obtain H-Ti-W-MC and H-Zr-W-MC inorganic porous crystals with different linkers;
[0017] or,
[0018] (B1) Add ammonium metatungstate and ammonium molybdate to KOH solution, stir, adjust pH, add VOSO4 solution, continue stirring, adjust pH again, heat to react, centrifuge, collect suspension, centrifuge again, dry solid, grind, and obtain KV-Mo 4-x -MC inorganic porous crystal, wherein x=3.2 to 4;
[0019] (B2) KV-Mo 4-x -MC inorganic porous crystals are mixed with water to form a suspension, the pH is adjusted, the reaction is stirred, centrifuged, washed, dried, and ground to obtain HV-Mo 4-x -MC inorganic porous crystal, wherein x=3.2-4.
[0020] Furthermore, in step (A1) and step (B1), the concentration of the KOH solution is 0.05 to 0.3 g / mL.
[0021] Furthermore, in step (A1) and step (B1), the pH is adjusted to 6 to 8 using sulfuric acid, and then the pH is adjusted to 3.8 to 4.2 using aqueous ammonia.
[0022] Furthermore, in step (A1) and step (B1), the heating reaction temperature is 165 to 180° C., and the heating reaction time is 15 to 30 hours.
[0023] Furthermore, in step (A1) and step (B1), the drying temperature is 60 to 100° C., and the drying time is 8 to 15 hours.
[0024] Furthermore, in step (A1), the mass ratio of KOH, ammonium metatungstate and VOSO4 is (1.5-3): (2-3): (1-2.5).
[0025] Furthermore, in step (A2), the mass ratio of KVW-MC to water is (1-2):(10-15).
[0026] Furthermore, in step (A2), the pH is adjusted to 1.2 to 1.5 using sulfuric acid.
[0027] Furthermore, in step (A2), the stirring reaction time is 2 to 3 hours.
[0028] Furthermore, in step (A2), the drying temperature is 80 to 100° C., and the drying time is 8 to 15 hours.
[0029] Furthermore, in step (A3), the mass ratio of KVW-MC, CsCl and water is (0.5-2):(0.5-2):(10-15).
[0030] Furthermore, in step (A3), the stirring reaction time is 1 to 3 hours.
[0031] Furthermore, in step (A3), the drying temperature is 80-100° C., and the drying time is 8-15 hours.
[0032] Furthermore, in step (A4), the concentration of the aqueous solution of Ti(SO4)2 or Zr(SO4)2 is 0.01 to 0.1 g / mL.
[0033] Furthermore, in step (A4), the mass ratio of Ti(SO4)2 or Zr(SO4)2, KVW-MC and water is (0.1-0.5):(0.5-2.5):(10-25).
[0034] Furthermore, in step (A4), the pH is adjusted to 0.7 to 0.8 using sulfuric acid.
[0035] Furthermore, in step (A4), the stirring reaction time is 1 to 3 hours.
[0036] Furthermore, in step (A4), the drying temperature is 80-100° C., and the drying time is 8-15 hours.
[0037] Furthermore, in step (B1), the mass ratio of KOH, ammonium metatungstate, ammonium molybdate and VOSO4 is (1.5-3): (2-3): (0.05-1.0): (1-2.5).
[0038] Furthermore, in step (B1), the stirring time is 5 to 15 minutes, and the stirring time is continued for 5 to 15 minutes.
[0039] Furthermore, in step (B2), KV-Mo 4-x -The mass ratio of MC to water is (1~2):(10~15).
[0040] Furthermore, in step (B2), the pH is adjusted to 1.2 to 1.5 using sulfuric acid.
[0041] Furthermore, in step (B2), the stirring reaction time is 2 to 3 hours.
[0042] The present invention also includes the use of the VW inorganic porous material of the present invention in catalytic oxidation of NO at room temperature.
[0043] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0044] (1) The present invention adopts hydrothermal synthesis and ion exchange methods to successfully prepare VW inorganic porous materials composed of transition metals and having both redox and acidic properties. The VW inorganic porous materials have a clear crystal structure, regular micropore channels, abundant acidic sites and redox sites, and exhibit excellent catalytic activity in NO oxidation at room temperature.
[0045] (2) The raw materials used in the method of the present invention are cheap and easy to obtain, the preparation process is simple, the operation is simple and quick, the energy consumption is low, there is no special requirement for equipment, and the additional environmental pollution is small, so that it has potential application prospects in the field of flue gas denitrification. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is a structural model diagram of HVW-MC prepared in Example 1;
[0047] Figure 2 This is a SEM image of the VW inorganic porous material prepared in Example 1;
[0048] Figure 3 XRD pattern of the VW inorganic porous material prepared in Example 1;
[0049] Figure 4 This is a graph showing the N2 adsorption results of the VW inorganic porous material prepared in Example 1;
[0050] Figure 5It is a graph showing the change of NO conversion rate of the HVW-MC catalyst prepared in Example 1, the comparative catalyst USY and the commercial catalyst VW / TiO2 with temperature and time at room temperature;
[0051] Figure 6 The graphs are the changes of NO conversion rate of HVW-MC, KVW-MC and Cs-VW-MC inorganic porous materials with different counter ions in the pores prepared in Example 1 with temperature and time at room temperature;
[0052] Figure 7 The graphs are the changes of NO conversion rate of HVW-MC, H-Ti-W-MC and H-Zr-W-MC inorganic porous crystals with different linkers prepared in Example 1 with temperature and time at room temperature;
[0053] Figure 8 HVW-MC and HV-Mo with different Mo contents in the structural units prepared in Example 1 0.2 -MC, HV-Mo 0.4 -MC, HV-Mo 0.6 -MC, HV-Mo 0.8 -MC inorganic porous crystals NO conversion rate changes with temperature and time at room temperature. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0055] Example 1 Preparation of KVW-MC Inorganic Porous Crystals
[0056] Take 2.1784g KOH in beaker A, add 30mL distilled water to dissolve, stir and add 2.67g ammonium metatungstate and continue stirring for 10min; take another beaker B and add 1.736g VOSO4, add 20mL water to dissolve; take sulfuric acid solution (2mol / L) and add it to beaker A to adjust the pH of the solution to neutral, stir for 10min; pour the blue VOSO4 solution in beaker B into beaker A and mix and stir for 10min. Add 30% ammonia water to adjust the pH to about 4, place the solution in a reactor for hydrothermal reaction at 175℃ for 24h. After cooling, centrifuge and collect the green suspension. After high-speed centrifugation, discard the supernatant, place the bottom solid in an 80℃ oven for drying for 10h, take it out, and grind it to obtain KVW-MC inorganic porous crystals.
[0057] Example 2 Preparation of HVW-MC Inorganic Porous Crystals
[0058] 1 g of KVW-MC inorganic porous crystal prepared in Example 1 was placed in 10 mL of distilled water, and the pH was adjusted to 1.5 with 2 mol / L sulfuric acid solution. After stirring for 3 h, it was centrifuged and washed, dried at 80°C, and ground to obtain HVW-MC inorganic porous crystal. Its structural model is shown in FIG. Figure 1 As shown. 16 ] 8- As a structural unit and VO 2+ As a linker, it forms an inorganic porous structure similar to type A molecular sieve with a pore size of about 0.5nm.
[0059] Example 3 Preparation of Cs-VW-MC Inorganic Porous Crystals
[0060] 1 g of CsCl was placed in 10 mL of distilled water and stirred until dissolved, 1 g of KVW-MC inorganic porous crystal prepared in Example 1 was added, stirred for 3 h, centrifuged and washed for more than 3 times, dried at 80° C., and ground to obtain Cs-VW-MC inorganic porous crystal.
[0061] Example 4 Preparation of H-Ti-W-MC Inorganic Porous Crystals
[0062] Take 0.5g Ti(SO4)2 solid and add it to 10mL distilled water, stir and dissolve. Take 2.5g KVW-MC inorganic porous crystal prepared in Example 1 and add it to 15mL distilled water to obtain KVW-MC suspension, drop Ti(SO4)2 solution into KVW-MC suspension, adjust the solution pH to about 0.8 with 2mol / L sulfuric acid, stir for 2h, centrifuge to remove supernatant, wash 3 times with 0.1mol / L sulfuric acid, then wash 3 times with water, remove supernatant, dry the solid at 80℃ for 10h, grind to obtain H-Ti-W-MC inorganic porous crystal.
[0063] Example 5 Preparation of H-Zr-W-MC Inorganic Porous Crystals
[0064] Take 0.5g Zr(SO4)2 solid, add 10mL distilled water, stir and dissolve, and obtain Zr(SO4)2 solution. Take 2.5g KVW-MC inorganic porous crystal prepared in Example 1, add 15mL distilled water to obtain KVW-MC suspension, drop Zr(SO4)2 solution into KVW-MC suspension, adjust the solution pH to about 0.8 with 2mol / L sulfuric acid, stir for 2h, centrifuge to remove supernatant, wash 3 times with 0.1mol / L sulfuric acid, then wash 3 times with water, remove supernatant, dry the solid at 80℃ for 10h, and grind to obtain H-Zr-W-MC inorganic porous crystal.
[0065] Example 6 HV-Mo 0.2 - Preparation of MC Inorganic Porous Crystals
[0066] Take 2.1784g KOH in beaker A, add 30mL distilled water to dissolve, stir and add 2.5365g ammonium metatungstate and 0.0883g ammonium molybdate, control the molar ratio of W and Mo to 19:1, and continue stirring for 10min; take another beaker B and add 1.736g VOSO4, add 20mL water to dissolve; take sulfuric acid solution (2mol / L) and add it to beaker A to adjust the pH of the solution to neutral, stir for 10min; pour the blue VOSO4 solution in beaker B into beaker A and mix and stir for 10min. Add 30% ammonia water to adjust the pH to about 4, place the solution in a reactor and hydrothermally react at 175℃ for 24h. Cool and centrifuge to collect the yellow-green suspension, discard the supernatant after high-speed centrifugation, and place the bottom solid in an 80℃ oven for drying for 10h, then take it out and grind it to obtain KV-Mo 0.2 -MC inorganic porous crystal. Take 1g KV-Mo 0.2 -MC inorganic porous crystals were placed in 10mL distilled water, and the pH was adjusted to 1.5 with 2mol / L sulfuric acid solution. After stirring for 3h, they were centrifuged and washed, dried at 80℃, and ground to obtain HV-Mo 0.2 -MC inorganic porous crystals.
[0067] Example 7 HV-Mo 0.4 - Preparation of MC Inorganic Porous Crystals
[0068] Take 2.1784g KOH in beaker A, add 30mL distilled water to dissolve, stir and add 2.403g ammonium metatungstate and 0.1766g ammonium molybdate, control the molar ratio of W and Mo to 9:1, and continue stirring for 10min; take another beaker B and add 1.736g VOSO4, add 20mL water to dissolve; take sulfuric acid solution (2mol / L) and add it to beaker A to adjust the pH of the solution to neutral, stir for 10min; pour the blue VOSO4 solution in beaker B into beaker A and mix and stir for 10min. Add 30% ammonia water to adjust the pH to about 4, place the solution in a reactor and hydrothermally react at 175℃ for 24h. Cool and centrifuge to collect the yellow-green suspension, discard the supernatant after high-speed centrifugation, and place the bottom solid in an 80℃ oven for drying for 10h, then take it out and grind it to obtain KV-Mo 0.4 -MC inorganic porous crystal. Take 1g K-V-Mo 0.4 -MC inorganic porous crystals were placed in 10mL distilled water, and the pH was adjusted to 1.5 with 2mol / L sulfuric acid solution. After stirring for 3h, they were centrifuged and washed, dried at 80℃, and ground to obtain HV-Mo 0.4 -MC inorganic porous crystals.
[0069] Example 8 HV-Mo 0.6 - Preparation of MC Inorganic Porous Crystals
[0070] Take 2.1784g KOH in beaker A, add 30mL distilled water to dissolve, stir and add 2.136g ammonium metatungstate and 0.3532g ammonium molybdate, control the molar ratio of W and Mo to 4:1, and continue stirring for 10min; take another beaker B and add 1.736g VOSO4, add 20mL water to dissolve; take sulfuric acid solution (2mol / L) and add it to beaker A to adjust the pH of the solution to neutral, stir for 10min; pour the blue solution in beaker B into beaker A and mix and stir for 10min. Add 30% ammonia water to adjust the pH to about 4, place the solution in a reactor and hydrothermally react at 175℃ for 24h. After cooling, centrifuge and collect the yellow-green suspension. After high-speed centrifugation, discard the supernatant, place the bottom solid in an 80℃ oven for drying for 10h, take it out, and grind it to obtain KV-Mo 0.6 -MC inorganic porous crystal. Take 1g KV-Mo 0.6 -MC inorganic porous crystals were placed in 10mL distilled water, and the pH was adjusted to 1.5 with 2mol / L sulfuric acid solution. After stirring for 3h, they were centrifuged and washed, dried at 80℃, and ground to obtain HV-Mo 0.6 -MC inorganic porous crystals.
[0071] Example 9 HV-Mo 0.8 - Preparation of MC Inorganic Porous Crystals
[0072] Take 2.1784g KOH in beaker A, add 30mL distilled water to dissolve, stir and add 1.869g ammonium metatungstate and 0.5298g ammonium molybdate, control the molar ratio of W and Mo to 7:3, and continue stirring for 10min; take another beaker B and add 1.736g VOSO4, add 20mL water to dissolve; take sulfuric acid solution (2mol / L) and add it to beaker A to adjust the pH of the solution to neutral, stir for 10min; pour the blue VOSO4 solution in beaker B into beaker A and mix and stir for 10min. Add 30% ammonia water to adjust the pH to about 4, place the solution in a reactor and hydrothermally react at 175℃ for 24h. After cooling, centrifuge and collect the yellow-green suspension. After high-speed centrifugation, discard the supernatant, place the bottom solid in an 80℃ oven for drying for 10h, take it out, and grind it to obtain KV-Mo 0.8 -MC inorganic porous crystal. Take 1g K-V-Mo 0.8 -MC inorganic porous crystals were placed in 10mL distilled water, and the pH was adjusted to 1.5 with 2mol / L sulfuric acid solution. After stirring for 3h, they were centrifuged and washed, dried at 80℃, and ground to obtain HV-Mo 0.8 -MC inorganic porous crystals.
[0073] All VW inorganic porous crystals prepared in Examples 1 to 9 were subjected to SEM analysis. Figure 2 shown. Figure 2 A uniform and regular cubic structure was observed in the pores, with a crystal size of approximately 40-50 nm. The introduction of different counter ions in the pores and the replacement of structural units and linker elements in the framework did not change the morphology and size of the VW inorganic porous material.
[0074] The VW inorganic porous crystals prepared in Examples 1 to 9 were subjected to XRD analysis. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the diffraction peaks mainly belong to the diffraction peaks of VW inorganic porous crystals. The diffraction peaks of the crystals after the introduction of different counter ions in the pores and the replacement of structural units and linker elements in the skeleton are completely consistent with those of VW inorganic porous crystals, and no other impurity peaks appear, indicating that these operations have not changed the original crystal structure of VW-MC.
[0075] The VW inorganic porous crystals prepared in Examples 1 to 9 were subjected to crystallographic data analysis. The relevant crystallographic data are shown in Table 1.
[0076] Table 1 Crystallographic data of VW inorganic porous crystals
[0077]
[0078]
[0079] The VW inorganic porous crystals prepared in Examples 1 to 9 were subjected to N2 adsorption experiments. The experimental process is as follows: The N2 adsorption experiment was conducted on a BELsorp Max system. Before the adsorption experiment, the material was heat treated at 175°C under vacuum conditions for 2.5 hours. The N2 adsorption measurement was performed at liquid nitrogen temperature (-196°C). The surface area and pore volume were estimated using the Brunauer-Emmett-Teller (BET) method and the t-plot method, respectively. The results are shown in Figure 2. Figure 4 As shown. Figure 4 It can be seen that all porous materials are adsorbed at log(p / p0)<-5, and the curve belongs to the type IV adsorption isotherm, indicating that the material has a microporous structure. The order of the specific surface area of the materials obtained from the nitrogen adsorption results is: HVW-MC (274m 2 / g)>KVW-MC(249m 2 / g)>Cs-VW-MC(64m 2 / g); H-Ti-W-MC(346m 2 / g)>H-Zr-W-MC(335m 2 / g)>HVW-MC(274m 2 / g); HVW-MC(274m 2 / g)>HV-Mo 0.6-MC(270m 2 / g)>HV-Mo 0.4 -MC(267m 2 / g)>HV-Mo 0.2 -MC(252m 2 / g)>HV-Mo 0.8 -MC(225m 2 / g). The pore volume order of the materials is HVW-MC (0.086cm 3 ·g -1 )>KVW-MC(0.078cm 3 ·g -1 )>Cs-VW-MC(0.032cm 3 ·g -1 ); H-Ti-W-MC(0.102cm 3 ·g -1 )>H-Zr-W-MC(0.099cm 3 ·g -1 )>HVW-MC(0.086cm 3 ·g -1 ); HVW-MC(0.086cm 3 ·g -1 )>HV-Mo 0.6 -MC(0.081cm 3 ·g -1 )>HV-Mo 0.4 -MC(0.079cm 3 ·g -1 )>HV-Mo 0.2 -MC(0.076cm 3 ·g -1 )>HV-Mo 0.8 -MC(0.072cm 3 ·g -1 ), which is consistent with the result of specific surface area.
[0080] Comparative Example 1
[0081] USY molecular sieve material, purchased.
[0082] Comparative Example 2
[0083] Take 0.51mmol of oxalic acid and add it to 2mL of water. After stirring to dissolve, add 0.17mmol of NH4VO3 and stir for 10min to obtain NH4VO3 solution. Take 0.99mmol of oxalic acid and add it to 2mL of water. After stirring to dissolve, add 0.028mmol of ammonium metatungstate and stir for 10min to obtain ammonium metatungstate solution. Add 1.4g of TiO2 to 20mL of water to make a uniform suspension, then add NH4VO3 solution and ammonium metatungstate solution. After stirring for 30min, heat at 120℃ to evaporate the water, and then dry in an oven at 100℃ to obtain a solid. The ground powder is placed in a muffle furnace and calcined at 450℃ for 4h to obtain the catalyst VW / TiO2.
[0084] Embodiment 20
[0085] The HVW-MC prepared in Example 1, the USY molecular sieve material in Comparative Example 1, and the VW / TiO2 in Comparative Example 2 were used as catalysts to carry out NO oxidation experiments.
[0086] (1) Changes of NO oxidation with temperature Experimental process: The catalytic reaction was carried out in a fixed bed quartz reactor. The catalyst particle size was 60-80 mesh and the dosage was 100 mg. The reaction gas composition was: 500 ppm NO, 5% O2, Ar as balance gas, and the gas space velocity was 60000 mL·h -1 ·g -1 cat. Before the reaction, the catalyst needs to be purged with high-purity Ar at 200°C for 0.5h. The catalytic reaction is carried out at 20-100°C, and the activity data is collected after the reaction reaches equilibrium. The NO conversion rate is calculated by the following formula (1):
[0087]
[0088] Among them, [NO] in represents the initial concentration of NO in the reaction gas at the reactor inlet, [NO] out It indicates the concentration of NO after the reaction.
[0089] The reaction results are as follows Figure 5 As shown in a, the catalytic activity of all catalysts gradually decreases with increasing temperature, and the activity is highest at room temperature. The catalytic activity of HVW-MC at room temperature is about 48%, which is much higher than the molecular sieve catalyst USY (7%) and the traditional VW / TiO2 catalyst (2%).
[0090] (2) Changes of NO oxidation over time Experimental process: The catalytic reaction was carried out in a fixed bed quartz reactor. The catalyst particle size was 60-80 mesh and the dosage was 100 mg. The reaction gas composition was: 500 ppm NO, 5% O2, Ar as balance gas, and the gas space velocity was 60000 mL·h -1·g -1 cat. Before the reaction, the catalyst needs to be purged with high-purity Ar at 200°C for 0.5 h. The catalytic reaction is carried out at room temperature, and the activity data are collected after the reaction reaches equilibrium.
[0091] The reaction results are as follows Figure 5 As shown in b, HVW-MC can maintain constant catalytic activity for more than 70 hours at room temperature. The room temperature catalytic activity of molecular sieve catalyst USY and traditional VW / TiO2 catalyst does not change with time, and is always less than 10%, which is much lower than HVW-MC inorganic porous crystal material.
[0092] Embodiment 21
[0093] The HVW-MC, KVW-MC and Cs-VW-MC prepared in Example 1 were used as catalysts for NO oxidation experiments to investigate the effects of different counterions in the pores on the NO catalytic oxidation performance at room temperature. Figure 6 shown. Figure 6 Figure a is a graph showing the change in NO conversion rate with temperature. The catalytic activity of all catalysts gradually decreases with increasing temperature. Figure 6 Figure b shows the change of NO conversion rate over time at room temperature. The catalytic activity of HVW-MC at room temperature is much higher than that of KVW-MC and Cs-VW-MC, indicating that the introduction of counterions with larger atomic radius into the pores is not conducive to the catalytic oxidation of NO.
[0094] Embodiment 22
[0095] The HVW-MC, H-Ti-W-MC and H-Zr-W-MC prepared in Example 1 were used as catalysts for NO oxidation experiments to investigate the effect of the replacement of different elements at the linker position in the molecular skeleton on the NO catalytic oxidation performance at room temperature. The results are as follows: Figure 7 shown. Figure 7 Figure a is a graph showing the change in NO conversion rate with temperature. The catalytic activity of all catalysts gradually decreases with increasing temperature. Figure 7 Figure b is a graph showing the change in NO conversion rate over time at room temperature. The catalytic activity of H-Zr-W-MC at room temperature is slightly higher than that of H-Ti-W-MC and slightly higher than that of HVW-MC, but the overall NO conversion rate remains between 50% and 60%, indicating that without changing the molecular pore structure, only changing the type of linker element in the molecular skeleton will not have much effect on the catalytic oxidation of NO, and a relatively high catalytic activity can still be maintained.
[0096] Embodiment 23
[0097] The HVW-MC and HV-Mo prepared in Example 1 0.2-MC, HV-Mo 0.4 -MC, HV-Mo 0.6 -MC and HV-Mo 0.8 -MC was used as a catalyst for NO oxidation experiments to investigate the effect of different Mo contents in the structural unit of the molecular skeleton on the NO catalytic oxidation performance at room temperature. Figure 8 shown. Figure 8 Figure a is a graph showing the change in NO conversion rate with temperature. The catalytic activity of all catalysts gradually decreases with increasing temperature. Figure 8 The figure (b) shows the change of NO conversion rate over time at room temperature. The NO catalytic activity of the Mo content between 0.4 and 0.8 is slightly higher than that of HVW-MC and HV-Mo. 0.2 -MC, but the overall NO conversion rate remained between 50% and 60%, indicating that without changing the molecular pore structure, only changing the type of structural unit elements in the molecular skeleton will not have a significant impact on the catalytic oxidation of NO, and a high catalytic activity can still be maintained.
Claims
1. A type of VW inorganic porous material, characterized in that: The anion molecular formula of the VW inorganic porous material is [W x Mo 4-x V y Zr 3-y O 19 ] 2- or [W x Mo 4-x V y Ti 3-y O 19 ] 2- , where x = 3.2 to 4, y = 2 to 3, and the counter cation is K + , Cs + and H + .
2. The VW inorganic porous material according to claim 1, characterized in that: [W x Mo 4-x O 16 ] 8- The tetrahedral structural unit and VO5 linker form a porous structure similar to type A molecular sieve, whose space group is PA-3 and the lattice parameter is 3. The VW inorganic porous material according to claim 1, characterized in that: VW Inorganic Porous Materials include:
4. The VW inorganic porous material according to claim 1, characterized in that: VW inorganic porous material has a cubic structure and the crystal size is about 40 to 50 nm.
5. The VW inorganic porous material according to claim 2, characterized in that: VW inorganic porous material exhibits NO oxidation activity at low temperature conditions of 20-100°C, with a NO conversion rate of 5-60%. It has excellent NO oxidation activity at room temperature and can maintain activity for more than 70 hours.
6. A method for preparing the VW inorganic porous material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (A1) mixing KOH solution and ammonium metatungstate, adjusting the pH, adding VOSO4 solution, continuing to stir, adjusting the pH again, heating to react, centrifuging, collecting the suspension, centrifuging again, drying, and grinding to obtain KVW-MC inorganic porous crystals; (A2) mixing KVW-MC inorganic porous crystals with water to form a suspension, adjusting the pH, stirring the suspension, centrifuging, drying, and grinding to obtain HVW-MC inorganic porous crystals; (A3) mixing KVW-MC inorganic porous crystals with water to prepare a suspension, adding CsCl, stirring for reaction, centrifuging, drying, and grinding to obtain Cs-VW-MC inorganic porous crystals; (A4) mixing KVW-MC inorganic porous crystals with water to prepare a suspension, dropping an aqueous solution of Ti(SO4)2 or Zr(SO4)2, adjusting the pH, stirring the reaction, centrifuging, acid-washing, water-washing, drying, and grinding to obtain H-Ti-W-MC and H-Zr-W-MC inorganic porous crystals with different linkers; or, (B1) Add ammonium metatungstate and ammonium molybdate to KOH solution, stir, adjust pH, add VOSO4 solution, continue stirring, adjust pH again, heat to react, centrifuge, collect suspension, centrifuge again, dry solid, grind, and obtain KV-Mo 4-x -MC inorganic porous crystal, wherein x=3.2 to 4; (B2) KV-Mo 4-x -MC inorganic porous crystals are mixed with water to form a suspension, the pH is adjusted, the reaction is stirred, centrifuged, washed, dried, and ground to obtain HV-Mo 4-x -MC inorganic porous crystal, wherein x=3.2-4.
7. The preparation method according to claim 6, characterized in that: In step (A1) and step (B1), the concentration of the KOH solution is 0.05-0.3 g / mL, the pH is adjusted to 6-8 with sulfuric acid, and then the pH is adjusted to 3.8-4.2 with ammonia water, the temperature of the heating reaction is 165-180° C., the time of the heating reaction is 15-30 h, the temperature of the drying is 60-100° C., and the time of the drying is 8-15 h.
8. The preparation method according to claim 6, characterized in that: In step (A1), the mass ratio of KOH, ammonium metatungstate and VOSO4 is (1.5-3): (2-3): (1-2.5), in step (A2), the mass ratio of KVW-MC and water is (1-2): (10-15), the pH is adjusted to 1.2-1.5 with sulfuric acid, the stirring reaction time is 2-3h, the drying temperature is 80-100°C, and the drying time is 8-15h; in step (A3), the mass ratio of KVW-MC, CsCl and water is (0.5-2): (0.5-2): (10-15), the stirring reaction time is The time is 1 to 3 hours, the drying temperature is 80 to 100°C, and the drying time is 8 to 15 hours; in step (A4), the concentration of the aqueous solution of Ti(SO4)2 or Zr(SO4)2 is 0.01 to 0.1 g / mL, the mass ratio of Ti(SO4)2 or Zr(SO4)2, KVW-MC and water is (0.1 to 0.5): (0.5 to 2.5): (10 to 25), the pH is adjusted to 0.7 to 0.8 with sulfuric acid, the stirring reaction time is 1 to 3 hours, the drying temperature is 80 to 100°C, and the drying time is 8 to 15 hours.
9. The preparation method according to claim 6, characterized in that: In step (B1), the mass ratio of KOH, ammonium metatungstate, ammonium molybdate and VOSO4 is (1.5-3): (2-3): (0.05-1.0): (1-2.5), the stirring time is 5-15 min, and the stirring time is continued for 5-15 min; in step (B2), KV-Mo 4-x The mass ratio of -MC to water is (1-2):(10-15), the pH is adjusted to 1.2-1.5 with sulfuric acid, and the stirring reaction time is 2-3 hours.
10. Use of the VW inorganic porous material according to any one of claims 1 to 6 in catalytic oxidation of NO at room temperature.